Differential expression of proteins associated with seasonal bud dormancy at four critical stages in Japanese apricot. (5th June 2012) - Zhuang, W.‐B.; Shi, T.; Gao, Z.‐H.; Zhang, Z.; Zhang, J.‐Y.
Abstract Dormancy is of great significance in the growth and development of deciduous fruit trees. We used a combination of two‐dimensional gel electrophoresis (2‐DE) and matrix‐assisted laser desorption/ionisation time of flight/time of flight mass spectrometry (MALDI–TOF/TOF MS) to identify the differentially expressed proteome of Japanese apricot flower buds at four critical stages, from paradormancy before leaf fall to dormancy release. More than 400 highly reproducible protein spots (P < 0.05) were detected: 34 protein spots showed a greater than twofold difference in expression values, of which 32 protein spots were confidently identified from databases. Identified proteins were classified into six functional categories: stress response and defence (11), energy metabolism (ten), protein metabolism (five), cell structure (three), transcription (one) and unclassified (two). The glyoxalase I homologue could help Japanese apricot survival under various abiotic and biotic stresses, greatly contributing to its dormancy. Enolase, thioredoxin family proteins and triose phosphate isomerase provide adequate energy to complete consecutive dormancy release and bud break in Japanese apricot. Cinnamyl alcohol dehydrogenase 9 and arginase enhance the resilience of plants, enabling them to complete dormancy safely. Analysis of functions of identified proteins and related metabolic pathways will increase our knowledge of dormancy in woody plants.